STORYTELLING SONGS OF THE ÈWÈ-DÒMÈ OF GHANA - Gbagbo, Divine Kwasi; Elder, D. Rose (International Library of African Music, 2019)
For the Central Èwè or Èwè-Dòmè people of Ghana’s Volta Region, storytelling is a vital practice used to transmit key lessons. For centuries the Èwè-Dòmè employed storytelling performances in initiation rites, war celebrations, wake-keeping, and praise singing to enrich the gathering by relaying important information, building group identity, and binding the community together with story, song, and dance. Storytellers and community participants point to the role that songs play within storytelling as cultural markers for the Èwè-Dòmè communities in the area around Ho, the Volta Region’s capital. Within the framework of extended family or town-wide storytelling performances, audience members habitually interrupt the story with song and dance that enlivens sleepy listeners and augments the story with an interpretive angle on the theme. Singing reverses the artist-audience roles. Other community events similarly provide an opportunity for artist-audience interaction and the reversal of roles. This paper documents the social role of songs in the context of storytelling as well as the performance practices, texts, melodies, rhythms, and harmonies of this important traditional musical genre in the face of numerous threats to its ongoing existence.
Keywords: Storytelling; Performance; Ewe (African people); Storytelling Session; Song Texts; Ghana; Song Interludes; African Music